The novel distribution of intracellular and extracellular flavonoids produced by Aspergillus sp. Gbtc 2, an endophytic fungus from Ginkgo biloba root - Wu, Xinhong; Zou, Kai; Liu, Xueduan; Fu, Shaodong; Zhang, Shuangfei; Duan, Zhenchun; Zhou, Jin; Liang, Yili (Frontiers in Microbiology, 2022)
Here we reported a Ginkgo endophyte, Aspergillus sp. Gbtc 2, isolated from the root tissue. Its flavonoid biosynthesis pathway was reconstructed, the effect of phenylalanine on the production of flavonoids was explored, and the flavonoid metabolites were identified with the high-resolution LC-MS. Some essential genes were annotated to form the upstream of the complete biosynthesis pathway, indicating that Aspergillus sp. Gbtc 2 has the ability to synthesize the C6-C3-C6 flavonoid monomers. HPLC results showed that adding an appropriate amount of phenylalanine could promote the production of flavonoids by Aspergillus Gbtc 2. LC-MS results depicted a significant difference in many flavonoids between intracellularly and extracellularly. Most of the flavonoids gathered in the cell contained glycosylation groups, while almost all components with multiple hydroxyls showed much higher concentrations extracellularly than intracellularly; they likely have different biological functions. A variety of these substances can be mapped back to the pathway pattern of flavonoid biosynthesis and prove the ability of flavonoid production once again. This study expanded the information on flavonoid biosynthesis in Aspergillus and provided a solid theoretical basis for developing the fungi into genetically engineered strains undertaking flavonoid industrialized production.